Effect of vibration analysis towards dynamic properties in dissimilar joining materials: A review - Rosmaliza, Mat Yaacob; Muhammad Zikri, Japri; N. A. Z., Abdullah; M. S. M., Sani (Faculty Mechanical Engineering, UMP, 2025)
This paper presents a comprehensive overview of vibration analysis in structures comprising dissimilar materials, highlighting the challenges and opportunities associated with various joining techniques and material selection. By exploring the impact of different joining methods on vibration performance, including factors such as structural design and dynamic characteristics, it synthesizes diverse methodologies employed in research on vibration analysis for jointed structures. Additionally, it explores the factors influencing the vibration performance of dynamic structures, focusing on structural joining techniques, material properties, and analytical methods. Through a systematic review, the study categorizes dissimilar joints into mechanical, thermal, and chemical joining processes, offering insights into their impact on vibration behavior and microstructural dynamics. By synthesizing research findings and methodologies, the paper underscores the significance of integrating experimental and numerical analyses to optimize the vibrational performance and reliability of joint structures, especially when dealing with dissimilar materials. This collaborative approach not only enhances predictive accuracy but also offers a deeper understanding of the intricate dynamics of jointed systems, fostering advancements in structural engineering and materials science. The paper also discusses the application of Finite Element Model Updating (FEMU) methods in vibration analysis to reduce uncertainties in model assumptions and enhance accuracy. FEMU involves iteratively refining numerical models to align with actual structural behavior, crucial for design, construction, and engineering applications. Various FEMU methods, including sensitivity-based approaches, iterative optimization, Bayesian techniques, and computational intelligence algorithms, offer effective means to update finite element models and minimize discrepancies between predicted and observed structural behavior. Despite computational challenges, these methods provide valuable tools for optimizing design and operational parameters in vibration analysis, advancing structural reliability and precision.